2021
DOI: 10.1186/s12966-021-01133-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of the PLAN-A intervention, a peer led physical activity program for adolescent girls: results of a cluster randomised controlled trial

Abstract: Background Physical activity is associated with improved health. Girls are less active than boys. Pilot work showed that a peer-led physical activity intervention called PLAN-A was a promising method of increasing physical activity in secondary school age girls. This study examined the effectiveness and cost-effectiveness of the PLAN-A intervention. Methods We conducted a cluster randomised controlled trial with Year 9 (13–14 year old) girls recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…The remaining four studies stated that they did not find evidence of cost-effectiveness. 84,90,92,98 Cost-effectiveness also varied by ethnicity, age, and socioeconomic status (SES). One study estimated lower ICERs for a multicomponent through-school physical activity and nutrition program in the M aori subpopulation and children in middle SES schools compared to the entire population and lower ICERs for older children across all subgroups compared with younger children.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining four studies stated that they did not find evidence of cost-effectiveness. 84,90,92,98 Cost-effectiveness also varied by ethnicity, age, and socioeconomic status (SES). One study estimated lower ICERs for a multicomponent through-school physical activity and nutrition program in the M aori subpopulation and children in middle SES schools compared to the entire population and lower ICERs for older children across all subgroups compared with younger children.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
“…31, One school or student was usually derived from study records, which included data such as intervention materials, cost of the venue for physical activities, teacher and trainer or facilitator time, travel and administration costs, and miscellaneous expenses. 97,98 The control arms were generally assigned no costs or negligible up-front costs. A prevalent costing assumption was that interventions operated in a steady state, not requiring one-off start-up costs.…”
Section: Study Characteristics Across All Intervention Groupingsmentioning
confidence: 99%
“…Of the six studies investigating physical activity as an outcome of interest, only one reported an increase in leaders' physical activity 37 , though this was measured via self-report. Where leaders' physical activity was assessed objectively (using pedometers or accelerometers), these interventions did not increase leaders' physical activity 10,45 . Several studies examined the effect of their intervention on leaders' self-reported diet and sedentary behaviours, though there was no evidence that school-based peer-led interventions reduce the sedentary behaviours of the leaders involved 53,54 .…”
Section: Academic Outcomes Meta-analysis-literacy Outcomesmentioning
confidence: 95%
“…Due to a lack of sufficient data, the corresponding meta-analyses were not conducted for behavioural and physical outcomes. The following potential categorical moderators of effects were identified after PROSPERO registration: (i) age (child [5][6][7][8][9][10][11][12] vs. adolescent [13][14][15][16][17][18]), (ii) study design (experimental vs. quasi-experimental), (iii) study duration (≤ 10 weeks vs. > 10 weeks) and (iv) congruence of age between leaders and peer recipients (same age vs. cross-age). Due to the homogeneity of moderators across the studies included in the meta-analyses (e.g., all studies in the meta-analyses had child leaders), we were not able to conduct moderator analyses.…”
Section: Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation